1995
DOI: 10.1530/eje.0.1320406
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of subtotal and total thyroidectomy in Graves' disease with and without endocrine ophthalmopathy

Abstract: A retrospective analysis was performed in 173 consecutive patients with Graves' disease (GD) with the principal aim of evaluating the influences of subtotal (N = 157) and total (N = 19) thyroidectomy on postoperative recurrence rates, endocrine ophthalmopathy (EO) and thyrotropin receptor antibody (TSH-R-ab) titres. Postoperatively recurrent disease, identified by increased thyroid hormone levels, occurred in 32 patients (20%) who underwent subtotal resection. These recurrences were associated with over-repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
3
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 21 publications
3
47
3
6
Order By: Relevance
“…They were significantly higher in the TT group than the ST group at 1, 3, 5, and 7 years after surgery, and the proportions were up to 70.4% at 6 months and 83.3% at 1 year. A relation between TRAb and endocrine opthalmopathy, and the probability of improving eye involvement by TT, were also reported by several authors [5,26,39]. As the number of patients who underwent TT for endocrine opthalmopathy was small (n = 22), we could not evaluate the influence of TT on opthalmopathy in this study.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…They were significantly higher in the TT group than the ST group at 1, 3, 5, and 7 years after surgery, and the proportions were up to 70.4% at 6 months and 83.3% at 1 year. A relation between TRAb and endocrine opthalmopathy, and the probability of improving eye involvement by TT, were also reported by several authors [5,26,39]. As the number of patients who underwent TT for endocrine opthalmopathy was small (n = 22), we could not evaluate the influence of TT on opthalmopathy in this study.…”
Section: Discussionmentioning
confidence: 64%
“…The continuation of a high (elevated) TRAb value or an increased TRAb value after surgery may cause hyperthyroidism recurrence [3,4]. In addition, previous studies demonstrated that a high TRAb value is linked to endocrine opthalmopathy [5,6], or risk for intrauterine death, and fetal or neonatal hyperthyroidism in pregnant women with Graves' disease [7][8][9][10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Eye disease worsened in 9 of 56 patients (16%) treated by subtotal thyroidectomy and 1 of 17 (6%) patients treated by total thyroidectomy, who had preoperative clinically evident ophthalmopathy, while new ophthalmopathy developed in 2 of 101 patients (2%) treated by subtotal thyroidectomy and 0 of 2 patients treated by total thyroidectomy (227). Thus, as a whole, progression of ophthalmopathy occurred in 12 patients (7%), more frequently among those who had clinically evident eye disease before surgery (227). No substantial effect on GO was observed by Miccoli et al (228) in 140 surgically treated Graves' patients, independently of the extent of thyroid resection.…”
Section: Thyroidectomymentioning
confidence: 98%
“…Winsa et al (227) recently evaluated retrospectively a large series of 173 Graves' patients who underwent either subtotal (n ϭ 157) or total (n ϭ 19) thyroidectomy. Eye disease worsened in 9 of 56 patients (16%) treated by subtotal thyroidectomy and 1 of 17 (6%) patients treated by total thyroidectomy, who had preoperative clinically evident ophthalmopathy, while new ophthalmopathy developed in 2 of 101 patients (2%) treated by subtotal thyroidectomy and 0 of 2 patients treated by total thyroidectomy (227).…”
Section: Thyroidectomymentioning
confidence: 99%